Root enhancement improves rhizosphere nutrient availability and promotes growth in flue-cured tobacco - Yu, Linyi; Zhang, Mingfa; Zhang, Sheng; Chen, Minggang; Yuan, Mouzhi; Huang, Jialing; Chen, Wenbo; Zhang, Yiyang (Frontiers in Plant Science, 2026)
IntroductionEnhancing root development can profoundly reshape rhizosphere symbioses that influence nutrient uptake and plant growth. However, the mechanisms linking root optimization, rhizosphere microbial assembly, and nutrient dynamics in flue-cured tobacco remain insufficiently understood.MethodsA field experiment was conducted using flue-cured tobacco (Nicotiana tabacum L., cv. Yunyan 87) to compare an enhanced-root treatment (nutrient-bag seedling system under alternating moisture) with conventional floating seedling cultivation. Root traits, rhizosphere nutrient availability, soil enzyme activities, microbial community composition, plant nutrient accumulation, and mediation relationships among root traits, rhizosphere environment, and plant growth were evaluated.ResultsThe enhanced-root treatment significantly increased root length and root volume (up to 65.6% and 51.5%, respectively). Rhizosphere function was improved, as indicated by higher available phosphorus (+51.7%) and urease activity (+29.6%). Microbial community composition shifted toward beneficial taxa, including enrichment of Rhizobiaceae and Actinobacteria. These changes were associated with greater nutrient acquisition, increasing total nitrogen, total phosphorus, and total potassium accumulation by 13–14%. Mediation analysis further demonstrated that the rhizosphere environment fully mediated the positive effects of root optimization on plant growth, supporting a causal chain of “root system → rhizosphere symbiosis → plant performance.”DiscussionStructural and functional enhancement of roots strengthens plant–microbe symbiosis and promotes nutrient cycling, thereby improving tobacco growth and nutrient accumulation. These findings provide a mechanistic framework for root-based strategies to enhance tobacco productivity while supporting soil ecological function.